(untitled) (IAHS Medical Journal, 2024)
Background: Knowledge of medical negligence and law related medical practice is mandatory for all healthcare professionals. The objective of the study to gaze the extent of knowledge and attitude of undergraduate medical students regarding this. Materials and methods: A cross-sectional survey was conducted during the period from July to October 2023 on 300 para-clinical and clinical medical students of Chattagram Maa-O-Shishu Hospital Medical College (CMOSHMC). A pretested questionnaire was used and data analyzed by SPSS V.22. Results: Out of 300 respondents from medical students of phase II, phase III and phase IV MBBS, the number of students were predominantly female and religion were Islam. The age range of the participants was from 20 – 25 years. Conclusion: The undergraduate medical students had a reasonable knowledge and positive attitude towards medical negligence and law related medical practice. However, the teaching of medical negligence and law related medical practice should be part of the medical curriculum to strengthen these attitudes. This will expose the students to the training classes using real case scenarios, workshops and seminars on medical negligence and law related medical practice, so that once they become doctors, they are not face difficulty in dealing with ethical issues. IAHS Medical Journal Vol 7(1), June 2024; 4-7